PEMETAAN TOTAL SUSPENDED SOLID (TSS) MENGGUNAKAN CITRA SATELIT MULTI TEMPORAL DI DANAU RAWA PENING PROVINSI JAWA TENGAH - Pinastika Nurandani; Sawitri Subiyanto; Bandi Sasmito (Jurnal Geodesi UNDIP, 2013)
Rawa Pening is a natural lake located in Central Java that vital existence. Quality and quantity of water are mayor concern. One of water quality parameter is Total Suspended Solid (TSS). TSS are solid materials, including organic and anorganic, that are suspended in the water. High concentration of TSS can reduce the penetration of sunlight into water bodies, increase water turbidity, and can settle at any time, causing silting.Distribution of TSS cab be identified using satellite remote sensing imagery. Metode used is development of modelling algorithms using regression equation of the relationship between the insitu value and reflectance of Landsat-7 ETM+ image at 2013. This research aims to determine the suitable empirical algorithm to estimate the concentration of TSS and mapping the distribution of TSS in Rawa Pening at 2002, 2007, and 2013.The research result shows that ratio between blue band and green band of Landsat-7 ETM+ using logarithmic regression are the most suitable algorithm for estimating TSS concentration in Rawa Pening. The equation are TSS=368,7ln(x)+31,52. Water Quality in Rawa Pening has decrease at 2007 compared to 2002, and increase at 2013.Keywords: Total Suspended Solid (TSS), remote sensing, Landsat-7ETM+, empirical algorithm, insitu, reflectance